EFEKTIFITAS JUS BUAH BIT TERHADAP PENINGKATAN KADAR HAEMOGLOBIN IBU HAMIL DENGAN ANEMIA - zuiatna, Dian Zuiatna; Nurrahmaton; Harahap, Ziadatun Amini (Politeknik Kesehatan Kemenkes Sorong, 2023)
Anemia in pregnant women occurs due to physiological changes and is exacerbated by malnutrition. One example of non-pharmacological treatment is using beets (Beta Vulgaris). The content of beets is Vitamin C, iron, zinc. The purpose of this study was to determine the effect of beetroot juice (beta vulgaris) on increasing hemoglobin levels in pregnant women with anemia in Sipaku Village, Area Simpang Empat District, Asahan Regency. The research design uses a Pre-Experimental Design approach in the form of One Group Pre-test and Post-test with a Paired t-test. The research population was 11 people. The sampling technique is non-probability sampling with purposive sampling technique. The results of the t test with a confidence level of 95% show that the P-value = 0.000